2017
DOI: 10.1590/1518-8345.1394.2851
|View full text |Cite
|
Sign up to set email alerts
|

Management changes resulting from hospital accreditation

Abstract: Objective: to analyze managers and professionals' perceptions on the changes in hospital management deriving from accreditation.Method: descriptive study with qualitative approach. The participants were five hospital quality managers and 91 other professionals from a wide range of professional categories, hierarchical levels and activity areas at four hospitals in the South of Brazil certified at different levels in the Brazilian accreditation system. They answered the question "Tell me about the management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 23 publications
(40 reference statements)
0
37
0
12
Order By: Relevance
“…Such changes can be exemplified with the standardization and mapping of care processes; the increase of physical structure and work organization; improvements in the management of hospital costs; positioning of strategic vision in the market; inclusion of participatory leadership, as well as other initiatives that promote quality management. 14 It is observed that the most evaluated dimension by the Nursing team was that of process, while the least favorable was the English/Portuguese J Nurs UFPE online., Recife, 12(6):1524-31, June., 2018 1530 structure, inferring the need for a more indepth analysis of the propositions contained in this item, such as the re-evaluation of the training model of professionals that provide assistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such changes can be exemplified with the standardization and mapping of care processes; the increase of physical structure and work organization; improvements in the management of hospital costs; positioning of strategic vision in the market; inclusion of participatory leadership, as well as other initiatives that promote quality management. 14 It is observed that the most evaluated dimension by the Nursing team was that of process, while the least favorable was the English/Portuguese J Nurs UFPE online., Recife, 12(6):1524-31, June., 2018 1530 structure, inferring the need for a more indepth analysis of the propositions contained in this item, such as the re-evaluation of the training model of professionals that provide assistance.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the nurse's role in the Accreditation process deserves to be highlighted, since this professional, as a team leader, has a direct link with the multiprofessional actions, with the definition of strategies for the necessary changes in the care process and operational models for the provision of care. 14 A study that identified and compared the work environment of nurses from an Accredited and a Non-Accredited hospital, through the Nursing Work Index -Revised -Brazilian Version (B-NWI-R), showed that the differences presented were in relation to the work and satisfaction with salary, because in the organization that did not undergo the Accreditation process, the nurses had a shorter working day and were more satisfied with the salary. 15 The culture of quality is an organizational good that must be shared systemically in health services.…”
Section: Resultsmentioning
confidence: 99%
“…Political and organizational commitment is necessary, addressing the needs for accessibility, safety, quality and cost-effectiveness. An adequate physical structure and environment, medical equipment and other resources often support the clinical care provided and therefore must be used safely (21)(22) .…”
Section: Discussionmentioning
confidence: 99%
“…Females dominate in the position of nursing manager, which correspond with the feminine characteristics inherent in the nursing profession (4) . The ages of these nurses and length of their training demonstrates the preference of HE of Paraná for nursing managers with greater personal and professional experience.…”
Section: Discussionmentioning
confidence: 99%